Integration of morpho-physico-biochemical traits with SSR and SRAP markers for characterization of castor genotypes of Indian origin - Akhila S. R; Sushil Kumar; Amar A. Sakure; Dipak A. Patel; Mukesh P. Patel (Oil Crop Science, 2022)
Castor (Ricinus communis L.) is an important tropical oilseed crop, whose oil has versatile, practical value, especially in industries. The present study aimed to estimate the nature and magnitude of variability in the castor germplasm concerning yield and its component traits and physico-biochemical characters. Seed yield per plant and oil content ranged from 80.90 ​g (ICS-165) to 248.30 ​g (RG-3216), and 34.7% (ICS-172) to 58.7% (JI-277), respectively. The iodine value of oil ranged from 76.36 (JI-370) to 89.84 (P2-135) with an average value of 83.02. The mean saponification value of oil was 182.24. The genotypic and phenotypic coefficients of variation were high for acid value, capsules on the main raceme, seed yield per plant, and total length of the main raceme. A positive association of porosity, average unit volume, and total length of the main raceme with seed yield per plant showed that these characters might be directly attributed to seed yield improvement. By Manhattan distances, the 30 genotypes were grouped into 3 clusters. Their genetic diversity was elucidated using SSR and SRAP markers. SRAP marker produced higher mean number of total bands (5.71), polymorphic bands (4.57), percentage polymorphism (83.10%), PIC (1.72), RP (5.90), mean RP (1.02), MR (5.71), EMR (4.57) and MI (1.44) values when compared to SSR (2.89, 2.11, 79.63%, 0.61, 1.90, 0.72, 2.89, 2.11 and 0.49, respectively) marker. The highest genetic distance (0.77) was between 48-1 and JI-370, which indicated that these genotypes could be used in biparental mating schemes, QTL map development, and hybridization programmes to increase oil content and quality for industrial purposes.